DFT Investigation of the Mechanism of Methoxycarbonylation of Styrene by Palladium Chloride - Shanti Gopal Patra; Aritra Saha; Pratim Kumar Chattaraj (Chemistry)
The alkoxycarbonylation of styrene by palladium chloride is studied employing the density functional theory (DFT). Initially, [PdCl3]– reacts with methanol to form the methoxy-bound intermediate, which undergoes β-hydride elimination to form the key intermediate [PdCl2H]–. Then, a 1,2-insertion reaction to styrene takes place to form linear and branched alkyl coordinated with the PdII. Then, CO coordination followed by a 1,1-insertion reaction leads to the formation of acyl intermediate. Next, the methanolysis leads to the formation of esters. Previous reports with other catalysts suggested the intermolecular/intramolecular transition state (TS) formation with a high activation barrier, and this step was the bottleneck. To the best of our knowledge, this is the first time we have considered a two-step mechanism for the alcoholysis of the ester formation mechanism. After coordination with the metal, the methanol undergoes oxidative addition to form the PdIV square pyramidal intermediate, followed by reductive elimination to form the ester with regeneration of the metal hydride active intermediate. Deeper insight into the nature of bonding at the TSs is obtained through energy decomposition with natural orbital for chemical valence (EDA-NOCV) and quantum theory of atoms in molecules (QTAIM).